2018
DOI: 10.3390/jof4020070
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Properties and Cytotoxicity of Endophytic Fungi from Symphonia globulifera (Clusiaceae)

Abstract: There is continuing need for new and improved drugs to tackle malaria, which remains a major public health problem, especially in tropical and subtropical regions of the world. Natural products represent credible sources of new antiplasmodial agents for antimalarial drug development. Endophytes that widely colonize healthy tissues of plants have been shown to synthesize a great variety of secondary metabolites that might possess antiplasmodial benefits. The present study was carried out to evaluate the antipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…There is continuing need for new and improved drugs to tackle malaria, which remains a major public health problem, especially in tropical and subtropical regions of the world (Ateba et al., ). However, compounds that are ultimately selected for development of new antimalarial drugs must meet the requirements of rapid efficacy to counter the spread of malaria parasites, safe drugs, and that do not show any overt toxicity to human health (Fidock et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is continuing need for new and improved drugs to tackle malaria, which remains a major public health problem, especially in tropical and subtropical regions of the world (Ateba et al., ). However, compounds that are ultimately selected for development of new antimalarial drugs must meet the requirements of rapid efficacy to counter the spread of malaria parasites, safe drugs, and that do not show any overt toxicity to human health (Fidock et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Ateba et al. () observed that extracts from Paecilomyces lilacinus , Penicillium , and Paecilomyces sp . exerted highly potent activities against chloroquine‐resistant P. falciparum (IC 50 < 1 µg/mL); extracts from Mucor falcatus and Aspergillus aculeatus showed moderate potency (IC 50 between 10 and 25 µg/mL), while the extract from Aspergillus tamarri was considered inactive (IC 50 > 100 µg/mL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaria is still one of the major causes of mortality and morbidity in the world with over 3.3 billion people living with the ongoing risk of transmission (Ateba et al, 2018). In 2016, about 91 countries reported ∼216 million new cases of malaria and 445,000 mortalities.…”
Section: Antimalarial Activitymentioning
confidence: 99%
“…In 2016, about 91 countries reported ∼216 million new cases of malaria and 445,000 mortalities. The people most affected by malaria are those people that live in the subtropical and tropical regions of the world, people from Southeast Asia and sub-Saharan Africa where ∼80% of cases of malaria recorded are traceable to Plasmodium falciparum (Ateba et al, 2018). The recent widespread of anti-drug resistant malaria parasites makes the search for alternative and new malarial treatment drugs urgent (D'alessandro, 2009).…”
Section: Antimalarial Activitymentioning
confidence: 99%